Time and frequency domain analysis of long-term heart rate variability in an experimental model of diet-induced metabolic syndrome. (14th October 2021) - Lozano, W M; Arias-Mutis, O J; Calvo, C J; Bizy, A; Such-Miquel, L; Chorro, F J; Zhao, J; Alberola, A; Zarzoso, M
Abstract: Background: Metabolic syndrome (MetS) is defined as the set of at least three of the following conditions: central obesity, elevation of triglycerides, decreased in high-density lipoproteins, systemic hypertension and glucose intolerance. MetS is linked with a high prevalence of cardiovascular disease, including sudden cardiac death and atrial arrhythmias, which may be a consequence of changes related to the structure, function and autonomic control of the heart. One of the underlying mechanisms responsible could be the alteration of sinus node automaticity. Heart rate variability (HRV) analysis is a useful non-invasive tool for evaluating alterations in neural control of cardiac automaticity. Purpose: To examine the changes in long-term HRV using time- and frequency- domain analyses in an experimental model of diet-induced MetS which develops all its components. Methods: Male NZW rabbits were randomly assigned to control (n=10) or MetS group (n=10), fed with high-fat (10% coconut oil and 5% lard) and high sucrose (15% dissolved in water) diet during 28 weeks. At week 28, 24 hour ECG recording was performed (eMotion Faros 180, Mega Electronics®, 1 kHz). We analyzed 60 minutes of RR time series, comparing day (from 8:00 to 19:59 h) and night (from 20:00 to 7:59 h), and quantified the standard parameters of time and frequency domains: 1) Time domain: RR, SDNN, triangular index (Ti), RMSSD and TINN; 2) Frequency domain: very low (VLF), low (LF), high frequency (HF), and LF/HF index. Multivariate analysis of variance (MANOVA, factorial model) was used for statistical analysis (p<0.05). Results: Time domain analysis showed a decrease in RR interval (p<0.001) and geometrical Ti (p=0.036) in MetS animals (Figure, A-B), indicative of an increased heart rate. The rest of parameters in the time domain (SDNN, RMSSD, TINN) were not modified. Further, in the frequency domain at FFT spectrum, we did find a significant decrease in the LF band (p=0.032) in MetS animals (Figure, C). The rest of the frequency domain parameters (VLF, HF and LF/HF index) remained unchanged. Conclusion: MetS decreased RR interval duration and triangular index, suggesting an increased sympathetic activity during day and night. Those changes were reflected in LF modifications, and might be attributable to a deficiency in sympathetic-parasympathetic control, which requires adjustments to maintain normal autonomic balance. Collectively, these results could give insight into the autonomic mechanisms that underlie increased atrial arrhythmia susceptibility in MetS. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Generalitat Valenciana, University of Valencia